A Krashen-Inspired Model for Arabic Language Immersion and Second Language Acquisition - Muhammad Fadhil Hadziq; Halimi Halimi; Faisol Faisol (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2025)
Arabic is highly important in Islamic education; however, many students struggle to speak fluently due to predominantly theoretical teaching approaches. This study examines the Arabic language immersion program atHasni Jambi, affiliated with Gontor, based on Stephen Krashen’s second language acquisition theory. The focus is on the implementation of Krashen’s five hypotheses: acquisition-learning, monitor, natural order, input, and affective filter. A qualitative case study method was employed, utilizing interviews, observations, and document analysis from teachers and students. The findings indicate that the immersion program encompasses all aspects of students’ daily lives, both inside the classroom—using direct methods, context, visuals, and gestures—and outside the classroom through activities in dormitories, dining halls, daily broadcasts, and competitions. Evaluation is conducted at multiple levels, from daily to annual assessments. The program has been shown to enhance fluency, spontaneity, and intrinsic motivation while reinforcing the natural use of Arabic. Its contribution lies in presenting an effective immersion model that can serve as a reference for other Islamic educational institutions to consistently improve Arabic speaking skills.